The guest list - Foley, Lucy (Novelist) (New York: William Morrow, 2020)
On an island off the coast of Ireland, guests gather to celebrate the joining of two people--the groom: handsome and charming, a rising television star; and the bride: smart and ambitious, a magazine publisher. As the champagne is popped and the festivities begin, resentments and petty jealousies begin to mingle with the reminiscences and well wishes. And then someone turns up dead."--
Keywords: Murder -- Investigation -- Ireland -- Fiction; Weddings -- Fiction; Islands -- Fiction; Ireland -- Fiction; Psychological fiction; Thrillers (Fiction); Detective and mystery fiction